Design and Validation of the Virtual Classroom Management Questionnaire - Keshavarz, Mohsen; Mirmoghtadaie, Zohrehsadat; Nayyeri, Somayyeh (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Effective classroom management methods are well known, but effective ways of managing classes of beginner teachers remain elusive. Classroom management refers to the wide range of skills and techniques that teachers use to ensure that classes are conducted without destructive student behavior. The present study is applied nonexperimental research. The purpose of this study was to design a tool to measure the effective management of the virtual classroom from the perspective of professors and students in e-learning and evaluate its validity and reliability. The research sample was taken randomly from all universities that make use of e-learning in Tehran, Iran, during the 2019–2020 semesters. The results show that the professional development of online classroom management is necessary for preparing teachers to teach in digital environments. The results of this research in the form of a validated questionnaire can be considered as an indicator for educators and students working in online environments, and this tool can be used for effective teaching and learning in the digital age.